Maintenance of Cyclonic Vortex During Monsoon Intraseasonal Oscillation: A View From Kinetic Energy Budget. Issue 7 (31st March 2022) - Li, Baosheng; Zhou, Lei; Qin, Jianhuang; Meng, Ze
Abstract: The Monsoon intraseasonal oscillation (MISO) is the predominant variability over the tropical Indian Ocean during the Indian summer monsoon. A cyclonic vortex plays a critical role in the northward propagation of MISO. Here, we find that the pronounced intraseasonal kinetic energy accompanying the vortex is attributable to the barotropic energy gain from the background circulation. In particular, due to the phase shift between vortex and low‐level horizontal wind convergence, the covariance of the intraseasonal easterly and downdraft reinforces the intraseasonal kinetic energy before vortex. In contrast, the interaction between westerly and updraft nourishes the kinetic energy after vortex. Overall, the nonlinear processes across different scales are vital for the energy exchange during MISO, and this is dynamically different from that of Madden‐Julian oscillations. It implies that although these two major intraseasonal oscillations share the same spatiotemporal scales over the Indian Ocean, they are controlled by fundamentally different dynamical processes. Plain Language Summary: The northward‐propagating monsoon intraseasonal oscillation (MISO) is the predominant variability in tropics during the Indian summer monsoon. Numerous studies have mentioned that the cyclonic vortex before MISO is vital to the MISO propagation. In this study, the kinetic energy budget for the cyclonic vortex during MISO is examined using reanalysis products. The composite results show that the main energy source is from the background circulation. In addition, the sum of the intraseasonal potential energy and the work done by the pressure gradient force is a moderate contributor to the kinetic energy, which is fundamentally different from the Madden‐Julian oscillation. Moreover, the advection and the energy conversion to eddies are sinks for the kinetic energy of MISO. An analysis of decomposed budget shows that the interaction between the intraseasonal easterly and downdraft benefits energy transfer from the background state before vortex. Conversely, after vortex, the energy conversion is mainly attributable to the interaction between intraseasonal westerly and updraft. The findings reveal that the multi‐time scale energy conversion results in the kinetic energy reinforcement, which is tightened with nonlinear processes. In all, such process understanding is critical for advancing the framework for northward‐propagating MISO. Key Points: Maintenance of the cyclonic vortex is mainly attributable to the energy conversion from the background kinetic energy The nonlinear interaction across different scales is vital for the energy exchange in Monsoon intraseasonal oscillation which is different from the linear processes in Madden‐Julian oscillation The phase shift between convection and vortex enables energy to transfer from the background to the intraseasonal cyclonic vortex